Investigating the Influence of Commedia Dell’Arte on Punch and Judy Shows and the Development of its Educational Aspect (Groundings Undergraduate, 2024)
Punch and Judy is a British puppet show known for its comic use of violence, but is this the only factor that contributed to this show’s durability? Looking at its socio-historical context, its influence from commedia dell’arte, and drawing on multiple theories, this paper explores Punch and Judy’s development from a form of pure entertainment to educational entertainment. However, it also argues that while it contributed to the entertainment and educational landscapes of its period, its educational value is condemned in light of contemporary moral standards.
Keywords: Punch and Judy; Commedia dell'arte; Theatre Studies; Historical Theatre; Education Studies